2020
DOI: 10.33448/rsd-v9i8.6365
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de formigas cortadeiras em campos de altitude no sul do Brasil

Abstract: Remanescentes do ecossistema Campos Altitude são encontrados na microrregião de "Campos de Lages", SC, sul do Brasil. O objetivo deste trabalho foi avaliar e identificar espécies de formigas cortadeiras que ocorrem em Campos de Altitude. O estudo foi realizado entre os meses de Agosto de 2012 e Dezembro de 2013, em 18 municípios da micro-região de "Campos de Lages", Santa Catarina, sul do Brasil. No total, 75 formigueiros de cortadeiras foram localizados, medidos e georreferenciados, apresentando 16 formigueir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…According to Oliveira et al (2020), soil chemical factors directly influence the floristic composition of a given phytogeographic formation. Thus, the floristic composition acts directly on the foraging behavior of leaf-cutting ants, due to the differentiated selectivity in the selection of materials for the covering of the different species of leaf-cutting ants (Giesel et al, 2020). The change in nutrient content represents a Research, Society and Development, v. 9, n. 9, e370997371, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.7371 11 determining factor for numerous factors, such as the floristic conformation existing in a given location.…”
Section: Resultsmentioning
confidence: 99%
“…According to Oliveira et al (2020), soil chemical factors directly influence the floristic composition of a given phytogeographic formation. Thus, the floristic composition acts directly on the foraging behavior of leaf-cutting ants, due to the differentiated selectivity in the selection of materials for the covering of the different species of leaf-cutting ants (Giesel et al, 2020). The change in nutrient content represents a Research, Society and Development, v. 9, n. 9, e370997371, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.7371 11 determining factor for numerous factors, such as the floristic conformation existing in a given location.…”
Section: Resultsmentioning
confidence: 99%
“…They carry the plant material into their nest and incorporate it into the fungal garden. This capacity to cut large quantities of fresh leaves makes leaf-cutting ants one of the most important herbivores in the Neotropics, causing damage and economic losses in agricultural systems [ 1 , 3 , 11 , 12 , 13 , 64 ]. Leaf-cutting ants are very selective regarding the plant material they carry to the nest and have the capacity to recognize organisms or substances that are harmful either to individuals or to their symbiont fungus [ 3 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, leaf-cutting ants can cause serious damage to these plantations, especially at the sapling stage [ 11 ]. The defoliation caused by ants significantly reduces wood production, causing a decrease in tree growth and also making the trees more vulnerable to attack by other pests [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Myrmicinae and Formicinae are the most representative subfamilies of ants in rocky grassland mountains, with 53% and 18% of the total species richness, respectively, but few data were reported about Ponerinae sub-family, which O. bauri is included (Costa et al, 2015). Some representatives of Myrmicinae from rocky grassland mountains are the leaf cutters ants Atta sexdens Linnaeus (Giesel et al, 2020; and as example of ants with sub-family Formicinae, Nakano et al (2013) reported the occurrence of Myrmelachista Roger in the Atlantic Forest of Southeastern Brazil and Lachnomyrmex nordestinus was found in tropical forest of Maranguape (Feitosa & Brandão, 2008). The characterization of the types of ants that inhabit this mountain is scarce.…”
Section: Introductionmentioning
confidence: 99%